2020
DOI: 10.1111/tbed.13636
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of atypical porcine pestivirus in a closed pig herd with subclinical infection

Abstract: Pestiviruses are highly variable RNA viruses within the family Flaviviridae and include several viruses causing major economic impacts, such as bovine viral diarrhoea viruses 1 and 2, border disease virus and classical swine fever virus (CSFV) (Cagatay et al., 2018). In 2015, a new pestivirus, named Atypical Porcine Pestivirus (APPV), was identified in healthy pigs (Hause et al., 2015). Thereafter, in two independent studies, an association of APPV with the clinical syndrome of congenital tremor was reported (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Horizontal as well as vertical transmission of APPV infection between domestic pigs is indeed very efficient (Cagatay et al., 2019) and pigs may shed virus in saliva, faeces, urine and semen for several months after infection, making mating a possible route of infection with APPV (Arruda et al., 2016; de Groof et al., 2016). The idea of APPV spread via semen as one possible route of infection is supported by a study on domestic pigs in which young sows presented with the highest E rns antibody reactivity, and this reactivity decreased with time (Grahofer et al., 2020). If it is assumed that wild boar has the same shedding and spreading pattern as domestic pigs, it could be speculated that wild boar sows, which have been mated, should have a higher antibody reactivity than non‐mated gilts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Horizontal as well as vertical transmission of APPV infection between domestic pigs is indeed very efficient (Cagatay et al., 2019) and pigs may shed virus in saliva, faeces, urine and semen for several months after infection, making mating a possible route of infection with APPV (Arruda et al., 2016; de Groof et al., 2016). The idea of APPV spread via semen as one possible route of infection is supported by a study on domestic pigs in which young sows presented with the highest E rns antibody reactivity, and this reactivity decreased with time (Grahofer et al., 2020). If it is assumed that wild boar has the same shedding and spreading pattern as domestic pigs, it could be speculated that wild boar sows, which have been mated, should have a higher antibody reactivity than non‐mated gilts.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the results obtained from Germany and Serbia, where 52% of the tested wild boars had APPV specific antibodies, are comparable to the present Swedish results. Interestingly, a study from Switzerland also using the same indirect APPV‐specific ELISA presented an occurrence of APPV antibodies of 93% in a closed APPV endemic herd of domestic pigs (Grahofer et al., 2020), suggesting that APPV has the potential to cause an extensive herd immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infection rate in the United States is as high as 15.8%, while it is only 2.4% in Germany [ 11 , 12 ]. One recent report indicated that the APPV seropositive rate was 93.1% in a closed swine herd with subclinical infection [ 13 ]. Genome sequence data for APPV in various countries has shown the genetic distance of these strains to be up to 21%, and the genetic divergence is more than 15.0% [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are therefore regarded as safer and more efficient promising candidates for a vaccine and have shown remarkable advantages compared with the attenuated, inactivated, and subunit vaccines. To date, infection experiments with APPV have only been performed on pregnant sows using organ homogenates from APPV-positive tissues to obtain the infected piglets, which is very difficult and time-consuming [ 2 , 13 , 25 ]. It would therefore be very helpful to find alternative laboratory animals for APPV research.…”
Section: Introductionmentioning
confidence: 99%